How safe are titanium clips for appendiceal base in laparoscopic appendicectomy? - Aparajita Saha; Girish K. Kullolli; Tejaswini Vallabha; Vikram Sindgikar (Al Ameen Medical College, 2020)
Background: The most important step in appendectomy is the closure of the stump. There a lot of variations to appendiceal stump closure as newer methods have been introduced although a consensus has not been reached as to which is best method. Aim: The aim of the study was to evaluate the safety and ease of use of titanium clips versus conventional knotting for appendiceal stump closure in laparoscopic appendicectomy. Methods: A total of 90 patients were included in this study, 45 in each group. The patients were divided into two groups- The first group included patients undergoing Endoclip closure (EC) and the second group included patients undergoing suturing (S). Results: In this study majority of patients belonged to the age group of less than 20 years, that is 57.8% in EC group and 40% in S group. In study group mean time of surgery was found to be 57.20+/-1.254 minutes. In control group it was 66.89+/-1.72 9minutes. P value was found to be significant. There were no intra operative or post-operative complications noted in both groups. Post-operative pain was comparable among both the groups. Conclusion: It can be concluded that titanium endoclips can be safely used for closure of appendiceal stump. It has several advantages like shorter time of surgery and lesser learning curve.